The role of energy systems on hydropower in Turkey - Yuksel, Ibrahim; Arman, Hasan; Demirel, Ibrahim Halil (E D P SCIENCES, 2017)
Over the last two decades, global electricity production has more than doubled and electricity demand is rising rapidly around the world as economic development spreads to emerging economies. Not only has electricity demand increased significantly, it is the fastest growing end-use of energy. Therefore, technical, economic and environmental benefits of hydroelectric power make it an important contributor to the future world energy mix, particularly in the developing countries. On the other hand, the hydropower industry is closely linked to both water management and renewable energy production, and so has a unique role to play in contributing to sustainable development in a world where billions of people lack access to safe drinking water and adequate energy supplies. In addition to, approximately 1.6 billion people have no access to electricity and about 1.1 billion are without adequate water supply. However, resources for hydropower development are widely spread around the world. Potential exists in about 150 countries, and about 70% of the economically feasible potential remains to be developed-mostly in developing countries where the needs are most urgent. This paper deals with renewable energy systems and the role of hydropower in Turkey.
Keywords: SUSTAINABLE DEVELOPMENT; BIOMASS; Energy & Fuels; Engineering